Participatory Livelihood and Care Interventions as Pathways to Health Promotion and Security: A Qualitative Community-Based Implementation Study in Rural Thailand - Ranee Wongkongdech; Maitree Tronsao; Adisorn Wongkongdech (International Journal of Environmental Research and Public Health, 2026)
Background: Health security among structurally vulnerable populations depends not only on healthcare access but also on livelihood stability, caregiving capacity, and social participation. Evidence on how community-engaged participatory interventions address social determinants of health in low- and middle-income settings remains limited, particularly regarding how such interventions are implemented, documented, and evaluated in practice. Methods: This qualitative implementation study examined a participatory livelihood and caregiving intervention in a rural Thai setting. Over a nine-month period, 50 core participants from structurally vulnerable households engaged in integrated livelihood and caregiving activities. Data were collected through field observations, participatory reflection meetings, implementation records, LINE-group communication archives, and voluntary household financial logs, and were analysed using inductive thematic analysis. Results: Findings revealed perceived improvements across four interconnected dimensions of well-being: caregiving capacity, social connectedness, livelihood flexibility, and household economic buffering. Participants more consistently described household stabilization achieved through reduced expenditure, resource sharing, and livelihood diversification than rapid income growth. Sustained group participation was associated with strengthened peer support networks and greater self-reported confidence in managing caregiving and household challenges; however, these findings rest on self-reported and predominantly qualitative evidence, with financial documentation available for only a small, non-random subset of participants. Conclusions: These exploratory findings suggest that community-engaged livelihood and caregiving interventions may strengthen multidimensional health security by supporting stabilization processes rather than delivering immediate economic gains. Relational support, adaptive implementation, and community participation emerged as candidate mechanisms linking policy intentions to community health responsiveness. Health policy frameworks in comparable low- and middle-income settings may benefit from incorporating structural and relational social determinants alongside income-based metrics, although confirmatory research with comparison groups is needed before these implementation-level insights can inform generalizable policy guidance.